2022
DOI: 10.3389/fphys.2022.850117
|View full text |Cite
|
Sign up to set email alerts
|

The Antiarrhythmic Mechanisms of Flecainide in Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a severe yet rare inherited arrhythmia disorder. The cornerstone of CPVT medical therapy is the use of β-blockers; 30% of patients with CPVT do not respond well to optimal β-blocker treatment. Studies have shown that flecainide effectively prevents life-threatening arrhythmias in CPVT. Flecainide is a class IC antiarrhythmic drug blocking cardiac sodium channels. RyR2 inhibition is proposed as the principal mechanism of antiarrhythmic action of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…Среди препаратов, применяемых в дополнение к базовой терапии бета-адреноблокаторами, наиболее часто в литературе упоминается флекаинид -антиаритмический препарат IС класса [5]. Этот препарат купирует не только суправентрикулярные эктопические аритмии, но и желудочковые нарушения ритма [19]. Механизмы подавления флекаинидом триггерной эктопической активности остаются предметом дискуссий [20,21].…”
Section: другая антиаритмическая терапияunclassified
“…Среди препаратов, применяемых в дополнение к базовой терапии бета-адреноблокаторами, наиболее часто в литературе упоминается флекаинид -антиаритмический препарат IС класса [5]. Этот препарат купирует не только суправентрикулярные эктопические аритмии, но и желудочковые нарушения ритма [19]. Механизмы подавления флекаинидом триггерной эктопической активности остаются предметом дискуссий [20,21].…”
Section: другая антиаритмическая терапияunclassified
“…The other class IC AADs (Flecainide and Propafenone) are mainly used for supraventricular arrythmias. An exception is their administration in catecholaminergic polymorphic ventricular tachycardia, because of their negative effect on the RYR2 calcium channel and sodium currents [ 67 ].…”
Section: Medical Therapymentioning
confidence: 99%
“…[ 57 ] Its therapeutic mechanism, however, is still unclear, and could be attributed to several mechanisms involving sodium channels and RyR2 blockade. [ 61 ] Moreover, a recent study has also suggested that flecainide’s interaction with certain genetic variants could lead to arrhythmogenesis, highlighting the necessity of further research on its pharmacological mechanism. [ 62 ]…”
Section: Advances In Catecholaminergic Polymorphic Ventricular Tachyc...mentioning
confidence: 99%